Pereira market scan - Pereira, L. (2019)
The increasing competitiveness of market search related with information needs led to several companies to invest in new forms of decision making and models applied to scientific methods to position them as market leaders and to extract added value. This study was conducted with the propose of developing a market tool to allow a deeper and more pragmatic analysis to clients value and clients life cycle in order to contribute to the competitiveness of companies with relevant outputs and increase the market share of his company in a more conscious, objective way. The findings of this study allowed to quickly identify and to mitigate the type of problems which affect the organization and thus provide benefits to all the stakeholders that are in interaction with organizations.